N and C Isotope Variations Along an Extreme Eutrophication and Salinity Gradient in the Coorong Lagoon, South Australia - Priestley, Stacey C.; Tyler, Jonathan; Liebelt, Savannah R.; Mosley, Luke M.; Wong, Wei Wen; Shao, Yuexiao; Woolston, Zara; Farrell, Mark; Welsh, David T.; Brookes, Justin D.; Collins, Alan S.; Keneally, Chris; et al. (Frontiers in Earth Science, 2022)
The Coorong Lagoon is a unique hydrological and depositional system at the terminus of the Murray-Darling Basin, Australia’s largest river system. It exhibits large salinity, nutrient and organic matter gradients, providing a modern analogue to study and validate the use of δ15N and δ13C as tracers of past and contemporary geochemical cycles in estuarine environments. To this end, water and surface sediment samples were analysed for particulate organic nitrogen (PON) and carbon (POC) concentrations, and the respective δ15N and δ13C signatures of particulate nitrogen and carbon. PON and POC exhibited positive relationships to chlorophyll-a, indicating the dominance of phytoplankton production upon suspended organic matter. There was also a general trend of increasing δ15N of PON (δ15NPON) values and decreasing δ13C of particulate carbon (δ13CPC) values with increasing salinity and eutrophication in the restricted South Lagoon. In a multiple linear regression for δ15NPON the best two predictors in combination are PON and C:N molar ratio, highlighting the importance of productivity and the type or source of organic matter. For δ13CPC the best two predictors are total dissolved phosphorus and latitude, suggesting influences from productivity and proximity to the ocean. Sediment δ15N values across the Coorong lagoon overlap with the δ15NPON in the water column, suggesting that PON derived from algal material represents the main source of nitrogen to lagoon sediments. We hypothesise that limited N loss via denitrification leads to PON being recycled almost exclusively to ammonium, due to low rates of nitrification and dominance of dissimilatory nitrate reduction to ammonium (DNRA). We propose that preferential volitilisation of 14N in ammonia increases the δ15N of ammonium assimilated by phytoplankton, thereby increasing the δ15N within suspended organic matter and surface sediment in the South Lagoon. By contrast, the gradient exhibited in δ13CPC data was countered by a relatively constant sedimentary organic carbon δ13C. Data from the Coorong therefore suggest that δ15N values in sediments can be used to infer palaeo-productivity in this hypereutrophic and hypersaline depositional environment; however, the measured δ13CPC may be influenced by δ13CDIC or preferential loss of 13C during sedimentation that alter the sedimentary δ13C record of organic carbon.